The Digital Humanist: A Critical Inquiry - Fiormonte, Domenico; Rockwell, Geoffrey, 1959-; Ferguson, Christopher (Christopher John); Schmidt, Desmond; Tomasi, Francesca; Numerico, Teresa; Project Muse; Project Muse. (Project Muse, 2020)
This book offers a critical introduction to the core technologies underlying the Internet from a humanistic perspective. It provides a cultural critique of computing technologies, by exploring the history of computing and examining issues related to writing, representing, archiving and searching. The book raises awareness of, and calls for, the digital humanities to address the challenges posed by the linguistic and cultural divides in computing, the clash between communication and control, and the biases inherent in networked technologies.A common problem with publications in the Digital Humanities is the dominance of the Anglo-American perspective. While seeking to take a broader view, the book attempts to show how cultural bias can become an obstacle to innovation both in the methodology and practice of the Digital Humanities. Its central point is that no technological instrument is culturally unbiased, and that all too often the geography that underlies technology coincides with the social and economic interests of its producers. The alternative proposed in the book is one of a world in which variation, contamination and decentralization are essential instruments for the production and transmission of digital knowledge. It is thus necessary not only to have spaces where DH scholars can interact (such as international conferences, THATCamps, forums and mailing lists), but also a genuine sharing of technological know-how and experience."This is a truly exceptional work on the subject of the digital....Students and scholars new to the field of digital humanities will find in this book a gentle introduction to the field, which I cannot but think would be good and perhaps even inspirational for them....Its history of the development of machines and programs and communities bent on using computers to advance science and research merely sets the stage for an insightful analysis of the role of the digital in the way both scholars and everyday people communicate and conceive of themselves and "others" in written forms -- from treatises to credit card transactions." ~Peter ShillingsburgThe Digital Humanist is not simply a translation of the Italian book L'umanista digitale (il Mulino 2010), but a new version tailored to an international audience through the improvement and expansion of the sections on social, cultural and ethical problems of the most widely used methodologies, resources and applications.
Preface: Digital humanities at a political turn? / Geoffrey Rockwell -- Introduction -- Part I. The socio-historical roots -- Technology and the humanities: a history of interaction -- Internet, or the humanistic machine -- Part II. Theoretical and practical dimensions -- Writing and content production -- Representing and archiving -- Searching and organizing -- Conclusions - DH in a global perspective.
Translation of: L'umanista digitale.
Issued as part of book collections on Project MUSE.
Includes bibliographical references (pages 229-254).
Description based on print version record.
Keywords: Humanities -- Technological innovations; Humanities -- Electronic information resources; Digital humanities; Electronic books; Electronic books